Transition Regions Based on Threshold Filter Approaches for Image Segmentation and Morphological Opertation - Sharma, Sameer Kumar; Chourasia, Bharti (International Journal of Computer Sciences and Engineering, 2019)
The proposed method breaks the color image into its individual color component and then fuzzy filter based canny Edge detection technique is applied. This technique depends on the fuzzy rule-based system using 2 X 2 window mask which is used to modify membership value of the image in different fuzzy sets (which means it will smoothen the image), and this filtered image is given as input to canny edge detection technique and finally after this morphological processing is used. The Performance Parameter becomes better by combining Fuzzy and Canny Edge Detection and also morphological operations. The results were compared with other edge detection techniques like interactive image segmentation by maximal similarity based region merging (MSRM) and Image segmentation using transition region. Therefore it is evident that the developed Algorithm provides Improved Performance parameters for detecting the edge against the wide range of Applications.